METODE BIMBINGAN MANASIK HAJI TERHADAP CALON JAMAAH HAJI DI KABUPATEN ENREKANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research raises the issue of what efforts or methods are carried out by the Bungin District Religious Affairs Office in guiding Hajj rituals to prospective Hajj pilgrims. With two sub-problems, namely: 1) What is the method of guidance for Hajj rituals at the Bungin District Religious Affairs Office? 2) What are the results of the Hajj ritual guidance at the Bungin District Religious Affairs Office? The research objectives are to find out and describe: 1) The efforts of the Bungin District Religious Affairs Office in carrying out Hajj ritual guidance, and 2) The results of Hajj ritual guidance services at the Bungin District Religious Affairs Office. This type of research is qualitative research with a Hajj management approach. The research location is the Religious Affairs Office, Bungin District, Enrekang Regency. The primary data sources in this research were the Head of the Bungin District Religious Affairs Office as a key informant, employees of the Bungin District Religious Affairs Office, and several prospective Hajj pilgrims as additional informants. Secondary data sources include documents, reports, archives, books, journals, and the internet. The data collection methods are observation, interviews, and documentation methods. Analysis of research data by data reduction, data presentation, and conclusion. The results of this research show that the Hajj ritual guidance methods implemented at the Bungin District Religious Affairs Office are: 1) Forming a Hajj ritual guidance implementation committee, 2) Scheduling Hajj Manasik times, 3) Preparing adequate facilities, 4) Carrying out Hajj ritual guidance. The results of the Hajj ritual guidance services at the Bungin District Religious Affairs Office are: 1) Prospective Hajj Pilgrims Understand the Mechanisms of the Hajj, 2) Prospective Hajj Pilgrims Understand the Procedures for Carrying out the Hajj Pilgrimage, 3) Prospective Hajj Pilgrims are ready and able to prepare their own Hajj Pilgrimage Needs Independently. The implications of this research are for the Head of the Bungin District Religious Affairs Office to continue to provide the best methods or efforts with the Bungin District Religious Affairs Office employees in carrying out guidance on the Hajj rituals which are carried out every year.